2013
DOI: 10.1159/000348802
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prostate-Specific Antigen Levels Differently Influence Prostate Cancer Detection Rates of Two Different 12-Core Prostate Biopsy Schemes

Abstract: Objective: To compare two 12-core transrectal ultrasound-guided prostate biopsy schemes in respect to cancer detection rates. Methods: Retrospective, single-center analysis of consecutive patients (n = 897) who underwent prostate biopsy (S1) with all 12 cores from far lateral areas (n = 269) or prostate biopsy (S2) with 6 cores from parasagittal and 6 from far lateral areas (n = 628). Results: Crude cancer detection rates with S1 and S2 were similar (39.0 and 38.9% for the first biopsy and 29.4 and 31.3% for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…In the subgroup analysis according to prostate volume, transition zone volume, serum PSA concentrations, and PSA density, a higher cancer detection rate was associated with decreased prostate volume and transition zone volume, and increased values of serum PSA concentration and PSA density. These results are consistent with recent studies suggesting that prostate volume [ 13 ] and PSA concentration [ 14 ] are associated with positive systematic biopsies. Interestingly, the positive midline biopsy rate was highest in the patients with a moderate prostate volume, ranging from 30 mL to 60 mL.…”
Section: Discussionsupporting
confidence: 93%
“…In the subgroup analysis according to prostate volume, transition zone volume, serum PSA concentrations, and PSA density, a higher cancer detection rate was associated with decreased prostate volume and transition zone volume, and increased values of serum PSA concentration and PSA density. These results are consistent with recent studies suggesting that prostate volume [ 13 ] and PSA concentration [ 14 ] are associated with positive systematic biopsies. Interestingly, the positive midline biopsy rate was highest in the patients with a moderate prostate volume, ranging from 30 mL to 60 mL.…”
Section: Discussionsupporting
confidence: 93%
“…The diagnosis of PCa depends on adequately sampling the zones in which cancer is mostly located (13). According to the literature, the 12 cores extended scheme remains the recommended standard in the initial PBx setting (14, 15). Guichard et al (4) found that the cancer detection rates of 6, 12, 18, and 21-cores biopsy were 31.7%, 38.7%, 41.5%, and 42.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%